Variasi Intensitas Kata Sifat Dalam Bahasa Madura - Harrifah Mardatillah; Ika Nurhayani; Hamamah (Center of Language and Cultural Studies, 2022)
The variations of Madurese intensifying adjective were investigated in this study. This qualitative study uses questionnaire as the main instrument to know the intensifying adjectives used by the participants. The participants were asked to translate some sentences from Indonesian to Madurese based on their daily conversations. The participants are native Madurese speakers aged between of 15-60 years. The study revealed that there were 28 variations of intensifying adjective in Madurese which consist of 17 variations of quality level, 3 variations using a determinerbefore adjective, 4 variations using a determinerafter adjective, 9 variations using a determiner and suffix, and 1 variation using a confix. In the comparative level, it can be divided into equative, comparative, and superlative. There are 5 variations fromcomparison of the equivalent level in Madurese, whilein the comparative level only one variation is done, it is the addition of lebbi ... deri ..., and the superlative level found 5 variations in the intensity of adjectives.